Sensory and consumer evaluation of lucuma powder as an ingredient for ice cream in the United States - Singh, Gaganpreet (Kansas State University, 2022)
The growing demand for natural and healthy foods has prompted the use of high-nutrition, low-calorie ingredients in food products. Superfoods consist of a variety of nutrients such as healthy fats, fiber, vitamins, and minerals. Due to the presence of such components, they are proposed to have several health benefits. Lucuma is a subtropical fruit, belonging to Sapotaceae family. It is an ancient fruit cultivated in Andean region of Peru, Chile, and Ecuador. Lucuma fruit is usually commercialized as pulp and/or powdered form. The lucuma powder form has not been studied extensively relative to its sensory characteristics. Therefore, the objectives of this study were 1) to investigate the aroma volatile profiles of lucuma powders from different sources, 2) to examine the sensory characteristics of lucuma powders from different sources when used in a finished product (i.e., ice cream), and 3) to investigate consumer liking of ice creams made with lucuma powders with different sensory profiles and compare them to a caramel ice cream product, considered more mainstream and familiar to the US consumers. Twelve lucuma powder samples from different sources were used to develop their aroma volatile profiles using gas chromatography – olfactometry. The volatile analysis generated 37 aroma active volatiles responsible for 27 different aroma notes. Naturevibe and Healthworks products were the most different products compared to the other manufacturers evaluated in this study. Based on PCA visualization, five lucuma powder samples: Naturevibe, Terrasoul, Healthworks, Herbazest and Superfood by MRM were selected as they differed the most from an aroma profile standpoint to move forward with application into a final product form (i.e., ice cream). Six highly trained descriptive sensory panelists developed a sensory lexicon to describe the sensory properties of lucuma ice cream, consisting of 31 attributes including appearance, aroma, flavor, aftertaste, and texture. Analysis of Variance (ANOVA) results for descriptive analysis showed that the lucuma ice cream samples were perceived to be mostly similar to each other and slightly different than the caramel ice cream. Only five attributes: color intensity (appearance), caramelized (aroma), brown sweet (flavor), chalkiness (texture) and grainy (texture) were found to be statistically different (p<0.05). A central location consumer test was performed using untrained panelists who were frequent ice cream users. Results showed that lucuma and caramel ice creams were perceived to be different by consumers, but the margin was small. This study confirms that variability exists between lucuma powders from different sources and helps understand the consumer perception towards lucuma ice cream, which shows that it may have a competitive opportunity in the US market. More than half of the consumers (57%) responded that they would definitely or probably buy lucuma ice cream, if available on shelves, after tasting and looking at a product concept. Further research can explore the sources of variability and its effects on products containing lucuma powder as an ingredient, and the study of consumer perception of lucuma powder applied into other finished products such as yogurts, smoothies, and baked goods.
Keywords: Lucuma; Gas chromatography; Lucuma ice cream; Sensory; Olfactometry